Examen especial a la cuenta caja bancos de la cooperativa de ahorro y crédito “San Miguel De Los Bancos” de la provincia de Pichincha, período julio – septiembre de 2013 . - Robles Largo, Laura Beatriz (2014)
This thesis is entitled: "SPECIAL BANK ACCOUNT REVIEW CASE COOPERATIVE SAVINGS AND CREDIT" SAN MIGUEL DE BANKS "PICHINCHA PROVINCE, PERIOD JULY - SEPTEMBER 2013". He was raised in order to develop the practical application of the Special Consideration for Cooperative Savings and Credit "San Miguel de los Bancos" whose activities to date have not been audited either internally or externally, in accordance with the rules and Auditing techniques, standards and other legal laws. Likewise was developed in consideration of the Rules of Academic System of the National University of Loja, prior to choose the degree of Engineer in Public Accounting and Auditing Accountant. The goals outlined in the cooperative savings and credit "Michael Banks" in the province of Pichincha, were struck to make special consideration to the cash account - banks, based on supporting documents and enabling could be established special consideration of the respective set period. It was made in order to establish the reasonableness of the balances in the financial statements of these accounts, evaluate internal control implemented in this institution and in compliance with the rules and other laws, the same was executed to meet as a graduation requirement prior to choose the degree of Engineer in Accounting and Auditing, Chartered Accountant - Auditor (CPA) in the National University of Loja, work development in accordance with Ecuadorian Auditing standards. Upon completion of the job and has a report about the special examination report to the account box - Cooperative banks credit unions "San Miguel de los Bancos"; It is therefore recommended to continue conducting both internal and external audits in order to perform control the administrative and financial management of savings and credit cooperative "San Miguel de los Bancos”, which facilitates decision-making.